Accommodation to Uncomfortable Patterns. (February 2013) - Haigh, Sarah M; Jaschinski, Wolfgang; Allen, Peter M; Wilkins, Arnold J
Grating patterns can cause discomfort and perceptual distortions. Individuals who experience discomfort and are susceptible to these distortions generally show weaker accommodation than those who are less susceptible. We measured the accommodative response to grating patterns known to differ in the discomfort they evoke because of differences in their colour, motion, or spatial frequency. The parameters known to affect discomfort and distortion had no influence on the mean or variance in the accommodative response, even when accommodative demand was manipulated systematically and the accommodative response varied as expected.